Microleakage of new glass ionomer restorative materials in permanent teeth - (:unkn) unknown (ARIESDUE SRL, 2014)
Aim The aim of this in vitro study was to evaluate the microleakage of the new glass ionomers ChemFil (TM) TmRock and lonoluxAC in comparison to Fuji IX GP Extra and the composite Aelite (TM) LS Posterior in permanent teeth. Materials and Methods Class V standardised U-shaped cavities were made on a total of 40 freshly extracted teeth and restored with different glass ionomer materials (4 groups of 10 samples each). After thermocyding, the teeth were immersed in 0.5% basic fuchsin for 24h. They were then sectioned in the buccolingual direction. Midoleakage was assessed for the ocdusal and gingival Margins under a microscope at 40x magnification. Results There were significant differences among the materials used (p=0.000). While there was no dye penetration in the Fuji IX GP EXTRA group, which behaved Similarly to the composite resin group, ChemFil (TM) Rock showed less microleakage than lonoluxAC. The Wilcoxon rank test shOwed no significant differences in the ocdusal and gingival scores between the groups (p>0.05). Conclusions Although cavities filled with a conventional glass ionomer (Fuji IX GP Extra) had significantly less leakage than cavities filled with the new glass ionomers (CherhFil (TM) Rock and lonoluxAC), these results do not reflect all the variables present in vivo conditions. As the in vitro evaluation of new materials does not always reveal their full limitations or possibilities, clinical testing of new systems remains the ultimate proof of effectiveness.
Keywords: Microleakage; Restorative materials; New and conventional Glass ionomers cements; SHEAR BOND STRENGTH; CLASS V CAVITIES; ADHESIVE SYSTEMS; LASER; COMPOSITE; ERBIUM